The Employment Situation of Media Professionals in Spain - García Salas, Ana Isabel (LABOS Revista de Derecho del Trabajo y Protección Social, 2026)
The nature of the work performed in the media sector, as well as the way in which that work is carried out, has characterized the approach and content of its labor relations for decades. To this must be added digital transformation, the emergence of new communicators, and the changes in employment that have occurred in our modern society. An exploration of these particularities and a legal analysis of the current situation, as a barometer of what is new and what is yet to come, constitute the raison d’être of this study.